Identification of Novel Inhibitors of Daboia russelli Phospholipase A2 Using the Combined Pharmacophore Modeling Approach. (3rd June 2014) - Ramakrishnan, Chandrasekaran; Joshi, Vikram; Joseph, Joseph Mavelithuruthel; Vishwanath, Bannikuppe S.; Velmurugan, Devadasan
<x xml:space="preserve">Abstract</x> Crystal structures available for Daboia russelli venom PLA2 confirm that it undergoes dimerization with asymmetry and hence difference in the conformation of active site of the two subunits. The active site of subunit A is open and that of subunit B is closed. Pharmacophore models were generated based on the interaction of different types of inhibitors with their preferred subsites in the active site of subunit A. Particularly, the features responsible for recognizing subsites 1–3 and those of subsites 4–6 were combined as these two are involving in inflammation and anticoagulation processes, respectively. Pharmacophore model was edited to make the geometry suitable for the active site of both the subunits A and B. Final model is validated and subjected for screening a library of druglike compounds. Eight compounds were shortlisted and subjected for molecular docking and dynamics simulation to assess their binding mode with both the subunits. Based on the hydrophobic interactions and binding free energy, four compounds were selected for further biochemical assay. The overall results suggest that two compounds can bind both the subunits of PLA2 of Daboia russelli venom in spite of its aggregated form and other two inhibit structurally very similar Naja naja PLA2.